Ginkgolide B promotes oligodendrocyte precursor cell differentiation and survival via Akt/CREB/bcl-2 signaling pathway after white matter lesion. Issue 10 (May 2021) - Huang, Jian; Yang, Jun; Zou, Xingju; Zuo, Shilun; Wang, Jing; Cheng, Jing; Zhu, Hao; Li, Weiwang; Shi, Ming; Zhao, Gang; Liu, Zhirong
White matter lesion (WML) is caused by chronic cerebral hypoperfusion, which are usually associated with cognitive impairment. Evidence from recent studies has shown that ginkgolide B has a neuroprotective effect that could be beneficial for the treatment of ischemia; however, it is not clear whether ginkgolide B has a protective effect on WML. Our data show that ginkgolide B can promote the differentiation of oligodendrocyte precursor cell (OPC) into oligodendrocytes and promote oligodendrocyte survival following a WML. Ginkgolide B (5, 10, 20 mg/kg) or saline is administered intraperitoneally every day after WML. After 4 weeks, the data of Morris water maze suggested that rats' memory and learning abilities were impaired, and the administration of ginkgolide B enhanced behavioral achievement. Also, treatment with ginkgolide B significantly attenuated this loss of myelin. Our result suggests that ginkgolide B promotes the differentiation of OPC into oligodendrocytes. We also found that ginkgolide B ameliorates oligodendrocytes apoptosis. Furthermore, ginkgolide B enhanced the expression of phosphorylated Akt and CREB. In conclusion, our data firstly show that ginkgolide B promotes oligodendrocyte genesis and oligodendrocyte myelin following a WML, possibly involving the Akt and CREB pathways.